Evolution of early male-killing in horizontally transmitted parasites - Bernhauerová, Veronika; Berec, Luděk; Maxin, Daniel (Proceedings. Biological sciences, 2015)
Early male-killing (MK) bacteria are vertically transmitted reproductive parasites which kill male offspring that inherit them. Whereas their incidence is well documented, characteristics allowing originally non-MK bacteria to gradually evolve MK ability remain unclear. We show that horizontal transmission is a mechanism enabling vertically transmitted bacteria to evolve fully efficient MK under a wide range of host and parasite characteristics, especially when the efficacy of vertical transmission is high. We also show that an almost 100% vertically transmitted and 100% effective male-killer may evolve from a purely horizontally transmitted non-MK ancestor, and that a 100% efficient male-killer can form a stable coexistence only with a non-MK bacterial strain. Our findings are in line with the empirical evidence on current MK bacteria, explain their high efficacy in killing infected male embryos and their variability within and across insect taxa, and suggest that they may have evolved independently in phylogenetically distinct species.
Keywords: fyziologie bakterií; reproductive parasite; horizontal transmission; hmyz; Host-Pathogen Interactions; interakce hostitele a patogenu; Biological Evolution; Female; zvířata; Sex Ratio; Insecta; přenos infekční nemoci; ženské pohlaví; Wolbachia; Male; biologická evoluce; Disease Transmission, Infectious; adaptive dynamics; Bacteria; poměr pohlaví; Animals; mužské pohlaví; Bacterial Physiological Phenomena; population dynamics; sex-ratio distortion